2021
DOI: 10.1142/s0192415x21500671
|View full text |Cite
|
Sign up to set email alerts
|

GABA- and Glycine-Mimetic Responses of Linalool on the Substantia Gelatinosa of the Trigeminal Subnucleus Caudalis in Juvenile Mice: Pain Management through Linalool-Mediated Inhibitory Neurotransmission

Abstract: Linalool, a major odorous constituent in essential oils extracted from lavender, is known to have a wide range of physiological effects on humans including pain management. The substantia gelatinosa (SG) of the trigeminal subnucleus caudalis (Vc) is involved in transmission of orofacial nociceptive responses through thin myelinated A[Formula: see text] and unmyelinated C primary afferent fibers. Up to date, the orofacial antinociceptive mechanism of linalool concerning SG neurons of the Vc has not been complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, linalool increased reactions to glycine and GABA. These results imply that linalool functions similarly to glycine and GABA, suggesting that it could be a viable target for the treatment of orofacial pain by boosting inhibitory neuronal transmission in the substantia gelatinosa of the trigeminal subnucleus caudalis [33].…”
Section: Anti-nociceptive Potentialmentioning
confidence: 83%
“…Moreover, linalool increased reactions to glycine and GABA. These results imply that linalool functions similarly to glycine and GABA, suggesting that it could be a viable target for the treatment of orofacial pain by boosting inhibitory neuronal transmission in the substantia gelatinosa of the trigeminal subnucleus caudalis [33].…”
Section: Anti-nociceptive Potentialmentioning
confidence: 83%
“…In addition, radioligand binding assay reveals that substances like (S) naringenin, glabrol, and 8-lavandulyl- flavanones act on the GABA receptors’ benzodiazepine site [ 50 ]. Besides flavonoid naringenin, essential oil linalool [ 51 ], terpene borneol [ 52 ], and biphenyl honokiol [ 53 ] possess the potential to influence the GABA receptor-mediated action on SG neurons of Vc. Notably, 6-hydroxyflavone, a flavone, shows diverse responses towards GABA, acting as a subtype-selective partial positive allosteric modulator at the flumazenil-sensitive benzodiazepine site and flumazenil-sensitive partial inverse agonist or negative modulator at α1β3γ2, α2β3γ2, and α5β3γ2 but not at α3β3γ2 receptor subunits [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that linalool has a wide range of physiological effects on humans including an anti-psoriatic effect, protects against the oxidative damage of UVB radiation of human skin cells by modulated NF-κB signaling and MAPK in HDFa cells, induces apoptosis in human leukemia cells, possesses sedative, anxiolytic and anticonvulsant proprieties by modulating the glutamate and GABA neurotransmitter systems, controls pain by potentiation with GABA- and glycine-induced responses and alleviates the side effects as well as tolerance to opioids (morphine) [ 2 , 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Unfortunately, its application is limited due to its lipophilicity (1590 mg/L in water at 25 °C), poor oral bioavailability and short half-life (about 44.72 min) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%